Quinazolinones linked amino acids derivatives as a new class of promising antimicrobial, antioxidant and anti-inflammatory agents - Rakesh, Kadalipura Puttaswamy; Ramesh, Suhas; Kumar, Honnayakanahalli Marichennegowda Manu; Chandan, Shivamallu; Gowda, Dase Channe (European Journal of Chemistry, 2015)
Two series of amino acids conjugated quinazolinones (1a-h and 2a-h) were synthesized by acid-amine coupling and the structures of all the compounds were confirmed through spectroscopic techniques such as IR, NMR and HRMS. The synthesized compounds were evaluated for their antimicrobial, antioxidant and anti-inflammatory activities. Biological evaluation study revealed that, the compounds 1f, 2f, 2g and 1g showed good antioxidant activity with 50% of the inhibition concentration (IC50) values 35, 20, 30 and 40 µg/mL, respectively, much better than the standard BHT (IC50 = 45 µg/mL). The compounds 1g, 2e and 2g found to have promising anti-inflammatory activity and almost all the synthesized compounds exhibited good antimicrobial activities (antibacterial and antifungal) against all the selected pathogenic bacteria and fungi. Conjugates containing Trp, Tyr and Pro have shown better activity than the rest of the analogues in the series. The structure-activity relationship was established for these compounds.